P41 ORAL ANTICOAGULATION AFTER REPAIR OF ACUTE TYPE A AORTIC DISSECTION: A REAL RISK ON LONG–TERM?. (18th May 2022) - Vendramin, I; Piani, D; Lechiancole, A; De Manna, N; Bressan, M; Sponga, S; Puppato, M; Muser, D; Bortolotti, U; Livi, U
Abstract: Objective: To analyse the effects of chronic oral anticoagulation on long–term outcomes after repair of type A acute aortic dissection and its influence on false lumen fate. Methods: We studied 188 patients (median age 62 years; 74% males) who had repair of type A aortic dissection; patients receiving postoperative chronic oral anticoagulation (n = 59) were compared to those on antiplatelet therapy alone (n = 129). Results: Median age was similar: 60 (18–79 years) vs 64 years (22–86) (p = 0.11); patients on anticoagulants were more frequently males (88% vs 67%, p = 0.003). After a median follow–up of 8.4 years (2 months to 30 years) 58 patients died, 18 for aortic–related causes, and 37 underwent aortic reintervention. After multivariable adjustment, anticoagulation showed no significant effect on long–term survival (HR 0.85, 95% CI 0.41–1.76; p = 0.66) neither on risk of reintervention (HR 0.55, 95% CI 0.27–1.15; p = 0.11). Analysis of 127 postoperative computed tomography scans showed a patent false lumen in 53% of anticoagulated vs 38% of not anticoagulated patients (p = 0.09); partially thrombosed in 8% vs 28% (p = 0.01) and thrombosed in 39% vs 34% (p = 0.63). In patients with a control computed tomography there were 6 late aortic–related deaths, 1 among patients anticoagulated and 5 in those who were not. Conclusions: Chronic anticoagulation after repair of type A acute aortic dissection favours persistent late false lumen patency which is not a risk factor for late mortality or reoperation. Chronic anticoagulation can be administered safely to patients with repaired type A acute aortic dissection regardless of its specific indication.